Reducing children’s anxiety and pain in dental environment using an eye massage device combined with natural sounds—a randomized controlled trial - Dajma Abed; Jamila Bchara; Dani Abed; Jina Alfeel; Nada Bshara (Scientific Reports)
Abstract This study evaluated the efficacy of an eye massage device that uses acupressure points combined with natural sounds to reduce anxiety and pain in children receiving dental anesthesia for the first time. A total of 105 children aged between 8 and 10 years whose dental treatment required inferior alveolar nerve block (IANB) injection participated in this randomized controlled clinical trial. The participants were randomly divided into three groups: Group A: eye massage with natural sounds; Group B: eye massage only; and Group C (control group): traditional behavior management techniques. Anxiety and pain were assessed before, during, and after anesthesia using the Children’s Fear Scale (CFS), Wong-Baker pain rating scale (WBS), the Face-Legs-Activity-Cry-Consolability (FLACC) observational pain assessment scale, and pulse rate as a physiological scale. Anxiety and pain significantly decreased in groups A and B compared with those in the control group (p < 0.05), with group A showing a greater decrease in pulse rate and objective pain assessed during injection via the FLACC scale than group B (p < 0.05); however, no significant difference was noted between groups A and B regarding the data recorded after anesthesia using the WBS and CFS (p > 0.05). Changes in pulse rate and anxiety levels (CFS) measured before and after the procedure in each group revealed a significant decrease in fear and pulse rate in group A and no significant change in group B, whereas group C showed a significant increase in pulse rate and fear at the end of the procedure. Eye massage with natural sounds can effectively alleviate children’s anxiety in the dental setting and reduce pain related to anesthesia, and the combination of these two interventions has the best relaxation effect on children.